Biosynthesis of tyrosine-derived i-melanin and its characteristics for organic thin film transistor device - Kim, Yoonjae; Park, Hyun A.; Lee, Pilwoo; Woo, Kyoungmin; Choi, Kwon Young; Lee, Hyun Ho (Materials Today Advances, 2025)
In this study, a novel symmetric indigo-derived melanin (i-melanin) was synthesized via the indigo dye biosynthetic pathway using MelC and CYP102G4 enzymatic reactions. Inspired by the symmetric dimer structure of indigo, 5,5′,6,6′-dihydroxyindigo was biosynthesized as a melanin monomer through enzymatic reactions catalyzed by indole oxygenase and sequential tyrosinase enzymes. This monomer underwent intracellular random polymerization, yielding a novel symmetric melanin. The structural and thermal characteristics of i-melanin were analyzed using FT-IR, SEM, and DSC, and a proposed structural model was presented. The resulting i-melanin exhibited both semiconducting and electrically conductive properties, making it a promising candidate for biocompatible semiconductor applications, such as thin-film transistors (TFTs) and bioelectronics. To characterize the electrical properties, the energy band gap of i-melanin was evaluated through density functional theory (DFT) calculations, UV–Vis spectroscopy, and photoluminescence (PL) spectroscopy. The electrical performance of i-melanin-based TFTs was further validated through current-voltage (I-V) and capacitance-voltage (C-V) measurements. These findings suggest that the newly designed biosemiconductor, synthesized via a biofactory system, has potential as a biocompatible and biodegradable alternative to synthetic organic semiconductors, with applications in transient and resorbable electronics.
Keywords: Biosemiconductor; C. thin film transistor (TFT); Cytochrome P450 monooxygenases; Enzymatic reaction; Indigo dye; Indigo-derived melanin; Organic thin film transistor devices; Symmetrics; Synthesised; Tyrosinase; Biosemiconductor; cytochrome P450 monooxygenase; i-melanin; TFT; tyrosinase